The other in the philosophy from the saemy side of absolute - Petrović, Aleksandar M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
In this review we take to considering the way of the constitution of human `I` in the shapes of a cogital moments of constitution, where is requested place of his coming to be and domestication. On a call of a Other, I (myself) have a meeting with him and coming into world with a wellcoming. Question of a freedom is positioned as a question of identity who is coming from the meeting with the Other, and from the moral of good will, who makes a modern subject as a most shining in a heritrage of a humanity.